High-Intensity Statin vs. Low-Density Lipoprotein Cholesterol Target for Patients Undergoing Percutaneous Coronary Intervention: Insights From a Territory-Wide Cohort Study in Hong Kong - Ng, Andrew Kei-Yan; Ng, Pauline Yeung; Ip, April; Siu, Chung-Wah (Frontiers in Cardiovascular Medicine, 2021)
Background: Different guidelines recommend different approaches to lipid management in patients with atherosclerotic cardiovascular disease. We aim to determine the best strategy for lipid management in Asian patients undergoing percutaneous coronary intervention (PCI). Method: This was a retrospective cohort study conducted in patients who underwent first-ever PCI from 14 hospitals in Hong Kong. All participants either achieved low-density lipoprotein cholesterol (LDL-C) target of <55 mg/dl with ≥50% reduction from baseline (group 1), or received high-intensity statin (group 2), or both (group 3) within 1 yr after PCI. The primary endpoint was a composite outcome of all-cause mortality, myocardial infarction, stroke, and any unplanned coronary revascularization between 1 and 5 yr after PCI. Results: A total of 8,650 patients were analyzed with a median follow-up period of 4.2 yr. After the adjustment of baseline characteristics, complexity of PCI and medications prescribed and the risks of the primary outcome were significantly lower in group 2 (hazard ratio [HR], 0.82; 95% confidence interval [CI], 0.74–0.93, P = 0.003) and group 3 (HR, 0.75; 95% CI, 0.62–0.90; P = 0.002). The primary outcome occurred at similar rates between group 2 and group 3. Conclusions: Use of high intensity statin, with or without the attainment of guidelines recommended LDL-C target, was associated with a lower adjusted risk of MACE at 5 yr, compared with patients who attained LDL-C target without high intensity statin.